Suono e immagine femminile: alcune domande - Ada Montellanico (Il sogno della farfalla, 2006)
The article proposes research into the historical and current reality of women in the musical world. In ancient history we find a great number of singers and instrumentalists who freely expressed themselves in Egypt, the Middle East, and Greece. Around the year 1000 BC we witness the first prohibitions and exclusions from the Jewish cultural milieu that continued and reached an apex of aberration and violence in 1588 when the Catholic church banned women from appearing on stage. After this historical excursus an attempt is made to try and understand this aversion over the centuries and why women have had great difficulty in approaching music. Is it a historical-cultural reality? Is it a diversity? The Greek myth in which Athena throws the aulos away after having seen her own face deformed when playing it, contrasts with M. Fagioli’s affirmation that it is the voice which represents the image of the woman who sings, not her face. The proposition of the voice as an image raises questions about the diverse attitude that exists between men and women in their attitude towards music. There have been many more women writers, painters and sculptors but very few composers, orchestra conductors or instrumentalists. Most have been interpreters, singers, musicians but interpreters. Is the difficulty women experience in composing music a diversity or must we consider it a handicap that needs to be resolved or overcome?